2015
DOI: 10.1097/prs.0000000000001369
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Cleft Lip Repair Using the Anatomical Subunit Approximation

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 57 publications
3
23
0
Order By: Relevance
“…As with rater reliability, the smaller range in magnitude of differences and the greater complexity of post-operative nasal deformity are likely contributed to the lower correlations after cleft lip repair. Similar to our previous study 20 , anthropometric measures after surgery tend to normalize (Figure 5), but with further time and growth, those differences become greater. Taken together, these three measurements may be used to quantify severity and outcome and could be used to follow longitudinal changes with time.…”
Section: Discussionsupporting
confidence: 87%
“…As with rater reliability, the smaller range in magnitude of differences and the greater complexity of post-operative nasal deformity are likely contributed to the lower correlations after cleft lip repair. Similar to our previous study 20 , anthropometric measures after surgery tend to normalize (Figure 5), but with further time and growth, those differences become greater. Taken together, these three measurements may be used to quantify severity and outcome and could be used to follow longitudinal changes with time.…”
Section: Discussionsupporting
confidence: 87%
“…21 As mentioned above, Millard's technique for cleft lip repair remains one of the most implemented and taught methods for correcting the cleft lip anomaly worldwide. 22 This also has been the case in in our institution. The anatomical subunit technique was introduced in the department by the senior author in 2015 and since then has been gaining popularity.…”
Section: Discussionsupporting
confidence: 79%
“…This finding was also true with other published studies indicating that with accurate application of the technique, the outcomes will less likely be affected by the severity of the cleft lip. 21,22,25 The high percentage of consanguinity (52%) in our study group highlight the need for targeted national campaigns involving premarital counselling regarding consanguinity especially as our study revealed that consanguineous families are more likely to have a 1 st degree relative with cleft lip. Two out of the eighty-two children were confirmed as syndromic, one was a case of Trisomy 21 and the other was diagnosed as Velocardiofacial syndrome.…”
Section: Discussionmentioning
confidence: 69%
“…The design of the repair [ 9 ] considers each anatomic subunit and attempts to place the lines of closure along the borders of subunits. One feature that differentiates it from other methods is the use of anatomic landmarks to define the design for repair [ 15 ]. As a result, the approach inherently adjusts to the spectrum of clefts ranging from wide complete to microform clefts.…”
Section: Discussionmentioning
confidence: 99%
“…Given that we assess surgical outcomes using anthropometric analysis, it makes sense that the repair should be based upon those same landmarks. While each surgeon should use the method that they are most comfortable with, the approach that we propose involves a “measure twice, cut once” style that has been associated with a reduced “learning curve” [ 15 ]. Those characteristics can be helpful given the rare nature of these clefts and the potential for asymmetric presentations.…”
Section: Discussionmentioning
confidence: 99%